Seasonal effects of water quality on infant and child health in India - Elizabeth Brainerd; Nidhiya Menon (Institute for the Study of Labor (IZA), 2012)
This paper examines the impact of fertilizer agrichemicals in water on infant and child health using data on water quality combined with data on the health outcomes of infants and children from the 1992-93, 1998-99, and 2005-06 Demographic and Health Surveys of India. Because fertilizers are applied at specific times in the growing season, the concentrations of agrichemicals in water vary seasonally and by cropped area as some Indian states plant predominantly summer crops while others plant winter crops. Our identification strategy exploits the differing timing of the planting seasons across regions and differing seasonal prenatal exposure to agrichemicals to identify the impact of agrichemical contamination on various measures of child health. The results indicate that children exposed to higher concentrations of agrichemicals during their first month experience worse health outcomes on a variety of measures (infant mortality, neo-natal mortality, height-for-age z scores and weight-for-age z-scores). Disaggregated runs reveal that effects are largest amongst the most vulnerable groups - children of uneducated poor women living in rural India.
urn:nbn:de:101:1-201301212408
Keywords: O12; I15; Q53; Q56; 330; fertilizer agrichemicals; water pollutants; child health; infant mortality; India; Gewässerbelastung; Düngemittel; Kinder; Gesundheit; Kindersterblichkeit; Indien